Ask me anything: Nicholas Attree. (1st November 2022) - Tesh, Sarah
Abstract : Nicholas Attree is a postdoctoral researcher at the Institute for Geophysics and Extraterrestrial Physics at the Technical University of Braunschweig in Germany, studying comets through the European Space Agency's Rosetta and Comet Interceptor missions.